PENINGKATAN HASIL BELAJAR IPA MELALUI MEDIA INTERAKTIF DIGITAL BERBASIS CHATBOT PADA SISWA KELAS IV 2 UPT SD NEGERI 8 BINAMU KECAMATAN BINAMU KABUPATEN JENEPONTO - Akram Mei Hasman; Nadrah Nadrah; Rahmatia Tahir (Universitas Maritim AMNI Semarang, 2023)
This study aims to describe the increase in science learning outcomes through chatbot-based digital interactive media in class IV 2 UPT SD Negeri 8 Binamu, Binamu District, Jeneponto Regency. The subjects used in this study were 40 students. The research procedure consists of 4 stages in each cycle, namely planning, action, observation and reflection. Indicators of learning outcomes in this study in the form of achieving classical learning mastery, namely 85%. As for data collection, namely the observation sheet and the final test of each cycle. The results of this study indicate that there is an increase in student learning outcomes, namely in the first cycle student learning outcomes obtained an average value of 67.5 with 45% mastery learning. In cycle II the average score is 75.75 with a mastery level of 87.5%. Thus, it can be concluded that the application of chatbot-based digital interactive media can improve science learning outcomes in class IV 2 UPT SD Negeri 8 Binamu, Binamu District, Jeneponto Regency.